Panduan mengesan bahan ilmiah Open Access Repository@USM (OAR@USM)/ePrints & Close Access Repository@USM (CAR@USM)/ DSpace - Perpustakaan, Hamzah Sendut (2017)
Guide to locate Scholarly Publications in Open Access Repository@USM (OAR@USM)/ePrints & Close Access Repository@USM (CAR@USM)/ DSpace